On the Failure of Hindsight-Biased Principals to Delegate Optimally - Danz, David; Kübler, Dorothea; Mechtenberg, Lydia; Schmid, Julia (Management Science, 2015)
With the help of a simple model, we show that the hindsight bias can lead to inefficient delegation decisions. This prediction is tested experimentally. In an online experiment that was conducted during the FIFA World Cup 2010, participants were asked to predict a number of outcomes of the ongoing World Cup and had to recall their assessments after the outcomes had been realized. Their answers were used to construct individual measures of the hindsight bias. The participants also had to make choices in a delegation game. Our data confirm that hindsight-biased subjects more frequently fail to delegate optimally than subjects whom we have classified as not hindsight biased. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.2087 . This paper was accepted by Teck-Hua Ho, judgment and decision making.